Production of a Functional Frozen Yogurt Fortified with Bifidobacterium spp. (11th June 2017) - Abdelazez, Amro; Muhammad, Zafarullah; Zhang, Qiu-Xue; Zhu, Zong-Tao; Abdelmotaal, Heba; Sami, Rokayya; Meng, Xiang-Chen
Abstract : Frozen dairy products have characteristics of both yogurt and ice cream and could be the persuasive carriers of probiotics. Functions of the frozen yogurt containing viable bifidobacterial cells are recognized and favored by the people of all ages. We developed a kind of yogurt supplemented by Bifidobacterium species. Firstly, five strains of Bifidobacterium spp. ( Bifidobacterium bifidum ATCC 11547, Bifidobacterium longum ATCC 11549, Bifidobacterium infantis ATCC 11551, Bifidobacterium adolescentis ATCC 11550, and Bifidobacterium breve ATCC 11548) were evaluated based on the feasibility criteria of probiotics, comprising acid production, bile tolerance, and adhesion to epithelial cells. Formerly, we combined the optimum strains with yogurt culture ( Lactobacillus delbrueckii subsp. bulgaricus EMCC 11102 and Streptococcus salivarius subsp. thermophilus EMCC 11044) for producing frozen yogurt. Finally, physiochemical properties and sensory evaluation of the frozen yogurt were investigated during storage of 60 days at −18°C. Results directed that Bifidobacterium adolescentis ATCC 11550 and Bifidobacterium infantis ATCC 11551 could be utilized with yogurt culture for producing frozen yogurt. Moreover, the frozen yogurt fermented by two bifidobacterial strains and yogurt culture gained the high evaluation in the physiochemical properties and sensory evaluation. In summary, our results revealed that there was no significant difference between frozen yogurt fermented by Bifidobacterium spp. and yogurt culture and that fermented by yogurt culture only.